Mitigasi Risiko Pembiayaan Mudharabah Studi BMT Assyafiiyah Berkah Nasional Kotagajah Perspektif Veithzal Rivai Tahun 2024 - Anwar, M. Syaiful; Farida, Annikamah; Khotamin, Nur Alfi; Rahmawati, Rita (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
Risk mitigation in mudharabah financing is a critical measure for Islamic microfinance institutions such as BMT Assyafi’iyah Berkah Nasional Kotagajah to maintain financial stability and reduce the risk of default. Risks such as moral hazard, information asymmetry, and limited member understanding of mudharabah contracts can significantly hinder financing operations. To address these challenges, the institution has implemented strategies including stringent screening of financing applicants by assessing business feasibility and financial history, conducting regular supervision, providing business mentoring, and educating members on the rights and obligations under mudharabah contracts. As a cooperative-based financial institution owned by its members, BMT Assyafi’iyah holds a significant responsibility to manage mudharabah financing in alignment with Islamic principles. The effectiveness of risk mitigation not only affects the operational sustainability of the institution but also the overall welfare of its members. This study aims to analyze the implementation of risk mitigation strategies in mudharabah financing at BMT Assyafi’iyah Berkah Nasional and evaluate their alignment with Veithzal Rivai’s risk mitigation principles. Using a descriptive qualitative approach and a case study method, data were collected through interviews, observations, and internal document analysis to gain a deep and contextual understanding. The findings indicate that although the institution has implemented key mitigation strategies—such as strict selection processes and business assistance—their effectiveness is still hindered by limited human resources, inadequate monitoring technology, and low member literacy regarding Islamic contracts. The study recommends capacity building, enhancement of technology-based monitoring systems, and intensive education for members. These findings provide valuable insights for other Islamic microfinance institutions aiming to improve the sustainability and Sharia compliance of their financing operations.